An Embedded Disk (eDisk) in the IceAge: Investigating the Jet and Outflow from Ced 110 IRS4 - Mayank Narang; Nagayoshi Ohashi; John J. Tobin; M. K. McClure; Jes K. Jørgensen; Jinshi Sai (Insa Choi); eDisk + IceAge Team (The Astronomical Journal)
We present a comprehensive study of the large-scale structure, jet and outflow morphology, and kinematics of the Class 0/I protostellar binary Ced 110 IRS4, using JWST NIRCam (F150W and F410M) and MIRI MRS observations from the JWST ERC program IceAge, along with Atacama Large Millimeter/submillimeter Array (ALMA) data from the Early Planet Formation in Embedded Disks (eDisk) program. NIRCam images, combined with ALMA continuum and CO data, reveal arc-like structures (∼1100 au), suggesting a dense envelope around the protostars. We detect disk shadows from both protostars in F150W. The MIRI MRS integral field unit data reveal a jet from both protostars in multiple [Fe ii ] lines, [Ar ii ] 6.99 μ m and [Ne ii ] 12.81 μ m, marking the first detection of a jet from the system. The [Fe ii ] (5.34 μ m) jet from Ced 110 IRS4A has a width of ≤51 au at the protostellar location, with a large opening angle of 23° ± 4°. After inclination correction, the jet velocity is 124 km s ^−1 , corresponding to a dynamical timescale of 25 yr. The molecular H _2 outflow displays a distinct morphology resembling two hemispheres placed back-to-back. The consistent H _2 emission extent across transitions, differing from previous observations of protostellar outflows detected with JWST, suggests that MHD disk winds may not drive the observed outflow. We find that the upper limit to the width of the outflow at the protostellar location is 130 ± 10 au, which is smaller than the disk diameter of 183.4 ± 0.4 au but much larger than width of the [Fe ii ] jet.